MICROWAVE-ASSISTED EXTRACTION OF TANNIN FROM PAPAYA LEAVES (CARICA PAPAYA LINN): THE EFFECT OF SOLVENT RATIO AND MICROWAVE POWER - Glen Bower Vebrianto Siregar; Early Akhalisty Inge Abigail Br Simanjuntak; Desi Riana Saputri; Yunita Fahni; Mustafa Mustafa; Rifqi Sufra; Reni Yuniarti; Fauzi Yusupandi; Faalih Pandu Wicaksono Hadi; Diana Catur Pratiwi; Putri Jesika Adelia; Vania Nur Wahdani; Angeline Nauli; Khofifah Anggitiya Ningrum; Misbahudin Alhanif (JURNAL INTEGRASI PROSES, 2024)
Papaya leaves (Carica papaya Linn) have many health benefits, such as antibacterial, anti-inflammatory, antidiarrhea, and others. Papaya leaves contain tannins, saponins, alkaloids, triterpenoids, steroids, and flavonoids. The common characteristic of papaya leaves is the green color, which indicates the presence of tannins. The study aims to discover the characteristics of papaya leaf extract, the effect of the solvent ratio, and the microwave power (MP) on the extraction of tannins from the papaya leaves. Papaya leaves are extracted using the microwave-assisted extraction (MAE) method at 100, 140, and 180 W for 30 minutes, with variations in the material to the solvent ratios 1:10, 1:20, 1:30, 1:40, and 1:50. Qualitative tannin testing was carried out through color observation and FeCl3 tests. UV-Vis spectrophotometry was also used to determine the tannin levels obtained during extraction. The FeCl3 test showed that papaya leaf extract contains tannins. The optimal concentration of tannins is produced at a ratio of 1:20, with a 180 W MP of 8.06 mg TAE/g and a yield of 0.81%. MAE can potentially increase the yield of tannins, which is potentially beneficial to health.